LDCs, agriculture, and food security - Glauber, Joseph W. (World Trade Organization, 2023)
According to the United Nations, least developed countries (LDCs) account for 13 per cent of the world population but only about 1.3 per cent of global GDP and less than 1 per cent of global trade and foreign direct investment . About 40 per cent of the world’s population living in extreme poverty can be found in LDCs. Most are suffering conflict or emerging from one.